Compassionate leadership in palliative and end-of-life care: a focus group study. Issue 2 (7th May 2019) - Hewison, Alistair; Sawbridge, Yvonne; Tooley, Laura
Abstract : Purpose: The purpose of this study was to explore compassionate leadership with those involved in leading system-wide end-of-life care. Its purpose was to: define compassionate leadership in the context of palliative and end-of-life care; collect accounts of compassionate leadership activity from key stakeholders in end-of-life and palliative care; and identify examples of compassionate leadership in practice. Design/methodology/approach: Four focus groups involving staff from a range of healthcare organisations including hospitals, hospices and community teams were conducted to access the accounts of staff leading palliative and end-of-life care. The data were analysed thematically. Findings: The themes that emerged from the data included: the importance of leadership as role modelling and nurturing; how stories were used to explain approaches to leading end-of-life care; the nature of leadership as challenging existing practice; and a requirement for leaders to manage boundaries effectively. Rich and detailed examples of leadership in action were shared. Research limitations/implications: The findings indicate that a relational approach to leadership was enacted in a range of palliative and end-of-life care settings. Practical implications: Context-specific action learning may be a means of further developing compassionate leadership capability in palliative and end-of-life care and more widely in healthcare settings. Originality/value: This paper presents data indicating how compassionate leadership, as a form of activity, is envisaged and enacted by staff in healthcare.